N, P or K doses on the dry matter and crude protein yield in maize and sorghum for silage - Damian, Júnior Melo (2017)
Maize and sorghum are the main raw materials in the production of silage for animal feed, with mineral fertilization being worthy of note when the goal is to increase gains in the amount and quality of the forage. This study aimed at evaluating the contribution of N, P or K doses to the dry matter and crude protein yield in maize and sorghum grown for silage. The experiments were carried out in a randomized block design, with four replications, during five successive crops of maize (three summer seasons) and sorghum (two off-season). Five doses of N (0 kg ha-1, 50 kg ha-1, 100 kg ha-1, 150 kg ha-1 and 200 kg ha-1), five doses of P2O5 (0 kg ha-1, 40 kg ha-1, 80 kg ha-1, 120 kg ha-1 and 160 kg ha-1) and five doses of K2O (0 kg ha-1, 30 kg ha-1, 60 kg ha-1, 90 kg ha-1 and 120 kg ha-1) were applied to each crop in the same experimental area. The N doses contributed to an increase in the crude protein yield in the five successive crops of maize and sorghum, together with an increase in dry matter and/or protein concentration. Crude protein increased 59.5-312.9 % for both crops. The soils used for the succession cropping system of maize and sorghum for silage had “very high” levels of P and K. Therefore, the P fertilization had no effect on the dry matter or crude protein yield in the first year of cultivation, similarly to the K fertilization during the five successive crop seasons.